Interplay between Notch1 and Notch3 promotes EMT and tumor initiation in squamous cell carcinoma. Issue 1 (December 2017) - Natsuizaka, Mitsuteru; Whelan, Kelly; Kagawa, Shingo; Tanaka, Koji; Giroux, Veronique; Chandramouleeswaran, Prasanna; Long, Apple; Sahu, Varun; Darling, Douglas; Que, Jianwen; Yang, Yizeng; Katz, Jonathan; et al.
Abstract Notch1 transactivatesNotch3 to drive terminal differentiation in stratified squamous epithelia. Notch1 and other Notch receptor paralogs cooperate to act as a tumor suppressor in squamous cell carcinomas (SCCs). However, Notch1 can be stochastically activated to promote carcinogenesis in murine models of SCC. Activated form of Notch1 promotes xenograft tumor growth when expressed ectopically. Here, we demonstrate that Notch1 activation and epithelial–mesenchymal transition (EMT) are coupled to promote SCC tumor initiation in concert with transforming growth factor (TGF)-β present in the tumor microenvironment. We find that TGFβ activates the transcription factor ZEB1 to repressNotch3, thereby limiting terminal differentiation. Concurrently, TGFβ drives Notch1-mediated EMT to generate tumor initiating cells characterized by high CD44 expression. Moreover, Notch1 is activated in a small subset of SCC cells at the invasive tumor front and predicts for poor prognosis of esophageal SCC, shedding light upon the tumor promoting oncogenic aspect of Notch1 in SCC. Notch receptors can exert different roles in cancer. In this manuscript, the authors reveal that Notch1 activation and EMT promote tumor initiation and cancer cell heterogeneity in squamous cell carcinoma, while the repression of Notch3 by ZEB1 limits Notch1-induced differentiation, permitting Notch1-mediated EMT.